2016
DOI: 10.1111/rssb.12192
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Designs for Longitudinal and Functional Data

Abstract: We propose novel optimal designs for longitudinal data for the common situation where the resources for longitudinal data collection are limited, by determining the optimal locations in time where measurements should be taken. As for all optimal designs, some prior information is needed to implement the proposed optimal designs. We demonstrate that this prior information may come from a pilot longitudinal study that has irregularly measured and noisy measurements, where for each subject one has available a sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 31 publications
0
32
0
Order By: Relevance
“…It is of interest to extend the proposed methods to select schedules that optimize power to detect associations between the longitudinal profiles and its correlates. While Ji and Müller () use predictive criteria for continuous outcomes to advance this area, we demonstrated that our proposed methods have power to detect associations between the profile and correlates even though the correlate was not specified in the design. Retout et al () evaluate the influence of designs on the power the Wald test has to detect a treatment effect in PMM.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It is of interest to extend the proposed methods to select schedules that optimize power to detect associations between the longitudinal profiles and its correlates. While Ji and Müller () use predictive criteria for continuous outcomes to advance this area, we demonstrated that our proposed methods have power to detect associations between the profile and correlates even though the correlate was not specified in the design. Retout et al () evaluate the influence of designs on the power the Wald test has to detect a treatment effect in PMM.…”
Section: Discussionmentioning
confidence: 92%
“…In B.1 and B.2, we de‐trend the data using local linear regression and only use the FPCA design method. Since in B.1 and B.2 the PMM is not applicable, use Ji and Müller ()'s idea to compare the FPCA to a ”random design.” Here, a random design consists of m times chosen from S at random without replacement. For all approaches, we use the Metropolis–Hastings algorithm described in Section to obtain T* for each preliminary data set.…”
Section: Simulation Studymentioning
confidence: 99%
“…Otherwise, if p is large, Ferraty et al . (), Ji & Müller () and Berrendero et al . () used a greedy search algorithm, and Wu et al () proposed a Metropolis sampling method.…”
Section: Methodsmentioning
confidence: 94%
“…While trueσ^ϵ2 might be close to zero in practice, we have not noticed such a case in the simulation studies and the real data applications. Should a very small estimate of error variance occur, we offer two options: (i) one may follow the approach in Ji & Müller () and select the estimate of error variance using cross‐validation of classification accuracy and (ii) approximate truebold∑^1=false{truer^false(boldt,boldtfalse)+trueσ^ϵ2boldIpfalse}1 by k=1trueK^trueλ^k1truebold-italicφ^ktruebold-italicφ^k, where truebold-italicφ^k=false{trueφ^kfalse(t1false),,trueφ^kfalse(tpfalse)false} and select trueK^ by cross‐validating the classification accuracy.…”
Section: Methodsmentioning
confidence: 99%
“…Whereas our study of relative efficiency has taken the design matrix X (and Z ) as given and considered av G ( ρ ) as a function of ρ , the field of optimal design is concerned with the choice of X . Depending on the choice of G and of nomenclature, av G (0) might be the criterion for an I ‐, V ‐ or I V ‐optimal or Q ‐optimal cross‐sectional design; see Ji and Müller and Park et al for recent contributions to optimal design for functional data. In neuroimaging and other biomedical studies of growth trajectories, we generally cannot “optimally design” the participants' ages.…”
Section: Discussionmentioning
confidence: 99%